Mechanism of crop growth promotion and responses to various environmental stresses with different plant extracts - Jang, Se Ji; Kuk, Yong In (Italian Journal of Agronomy, 2019)
Our objective in this study was to determine to what degree macro and micro nutrients in water extracts, ethanol extracts and whole plant applications of Chinese chive (CC), soybean leaf (SL) and soybean stem (SS) promoted crop growth and if growth promotion was related to physiological elements such as photosynthetic efficiency. The studies we conducted in Suncheon, South Korea in 2017 also sought to confirm crop responses to abiotic and biotic stresses after treatment with CC, SL and SS extracts. We found that most nutrient levels in CC, SL and SS water extracts were higher than in ethanol extracts. Thus, growth promotion effectiveness may be related to plant extraction method, but not to the plants themselves or to physiological elements. Boiled water extracts of SL at 5% suppressed some fungi by 92% (Bortytis cinereal) and 57% (Colletotrichum coccodes), however several others were not effectively suppressed. Compared to the control, rice plant injuries induced by 50 mM NaCl were reduced by 20- 39%, 41-46%, and 40-46% in response to CC, SL and SS extract treatments at 0.5, 1, and 3%, respectively. Shoot fresh weight of rice subjected to 50 mM also increased by 38%, 15-52%, and 40- 59% in response to treatments of CC, SL or SS extracts at 0.5, 1, and 3%, respectively. Rice injuries under drought conditions were reduced 20-26% in response to treatment with CC, SL and SS extracts at 1, 3, and 5% when compared with control plants. Furthermore, the shoot fresh weight of rice under drought conditions was 3.6, 2.0, and 3.2 times greater when treated with CC, SL and SS extracts at 5%, respectively. Thus, the CC, SL and SS extracts used in this study mitigate salt and drought stresses and fungicidal effects, as well as promoting crop growth and could therefore contribute substantially to sustainable crop production.